2015
DOI: 10.2147/cia.s85319
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of compliance and preference in Alzheimer’s disease treatment

Abstract: PurposeRivastigmine transdermal patch has shown higher caregiver satisfaction and greater preference than oral formulation in patients with Alzheimer’s disease. However, there is limited literature available related to caregiver preference or treatment compliance in real-world clinical settings. To date, no such data are available from Asia and the Middle East, which account for a sizeable proportion of patients with Alzheimer’s disease. The objective of this study was to evaluate treatment preference and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…The overall patient compliance in the current study was good in both the treatment cohorts, unlike other studies including AXEPT 20 and global RECAP 13 that showed greater patient compliance with rivastigmine transdermal patch over other oral medications as indicated by the caregivers of patients with AD. Results from the ENTERPRISE study 21 also showed high compliance rates (60.5%) with transdermal rivastigmine patch compared with the oral formulation.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…The overall patient compliance in the current study was good in both the treatment cohorts, unlike other studies including AXEPT 20 and global RECAP 13 that showed greater patient compliance with rivastigmine transdermal patch over other oral medications as indicated by the caregivers of patients with AD. Results from the ENTERPRISE study 21 also showed high compliance rates (60.5%) with transdermal rivastigmine patch compared with the oral formulation.…”
Section: Discussioncontrasting
confidence: 71%
“…Previously, the IDEAL, 12 Alzheimer disease: eXamination of patiEnt comPliance and caregiver satisfacTion (AXEPT), 20 Effective Management of Alzheimer’s Disease By TReating pAtients and relieving Caregivers with Exelon Patch (EMBRACE), 19 ENTERPRISE, 21 global RECAP study, 13 and an observational clinical study 22 have assessed the caregiver preference and/or satisfaction for the treatment of AD. IDEAL was the first pivotal trial 17 , 23 to demonstrate the non-inferiority of the rivastigmine transdermal patch over oral capsules; the study 12 also showed higher caregivers’ preference (72%) for the rivastigmine transdermal patch compared with oral capsules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations